Analisis Faktor-Faktor yang Memengaruhi Minat Nasabah pada Tabungan Islamic Banking (IB) Hijrah Haji pada Bank Muamalat Indonesia KC Kota Bengkulu - Septen Mardiah; Nonie Afrianty; Makmur (CV Global Research Publication, 2026)
This study aims to analyze the influence of cultural, social, personal, and psychological factors on customer interest in Islamic Banking (IB) Hijrah Hajj Savings at Bank Muamalat Indonesia Branch Office Of Bengkulu City. The study employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to 50 customers of IB Hijrah Hajj Savings selected using a purposive sampling technique. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS version 26.The results indicate that cultural, social, personal, and psychological factors partially and simultaneously have a positive and significant effect on customer interest in IB Hijrah Hajj Savings. Among these variables, psychological factors were found to be the most dominant factor influencing customer interest. The coefficient of determination (R²) value of 0.789 shows that 78.9% of the variation in customer interest can be explained by the four independent variables, while the remaining 21.1% is influenced by other factors outside the scope of this study. Based on the findings, Bank Muamalat Indonesia KC Bengkulu City is recommended to strengthen educational and promotional programs regarding the benefits of IB Hijrah Hajj Savings and to emphasize psychological and religious aspects in its marketing strategies. In addition, the public is encouraged to enhance awareness of early Hajj financial planning through savings products that comply with Islamic principles.